2013
DOI: 10.12688/f1000research.2-158.v2
|View full text |Cite
|
Sign up to set email alerts
|

The nociceptive withdrawal reflex does not adapt to joint position change and short-term motor practice

Abstract: The nociceptive withdrawal reflex is a protective mechanism to mediate interactions within a potentially dangerous environment. The reflex is formed by action-based sensory encoding during the early post-natal developmental period, and it is unknown if the protective motor function of the nociceptive withdrawal reflex in the human upper-limb is adaptable based on the configuration of the arm or if it can be modified by short-term practice of a similar or opposing motor action. In the present study, nociceptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…For these reasons, the early-latency enhancement of motor excitability observed at ISI=100 ms was most probably related to a segmental effect of Ad fiber nociceptive input on the excitability of spinal motoneurons. Although less investigated than in the lower limb, upper limb nociceptive reflex activities can be recorded following noxious electrical stimulation of the ulnar nerve as well as the fingers (Cambier et al, 1974;Bromm and Treede, 1980;Campbell et al, 1991;Bouhassira et al, 1993;Floeter et al, 1998;Serrao et al, 2006Serrao et al, , 2012Eckert and Riley, 2013). Such as for the lower limbs, this reflex activity could constitute a protective withdrawal response (Serrao et al, 2006;Peterson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, the early-latency enhancement of motor excitability observed at ISI=100 ms was most probably related to a segmental effect of Ad fiber nociceptive input on the excitability of spinal motoneurons. Although less investigated than in the lower limb, upper limb nociceptive reflex activities can be recorded following noxious electrical stimulation of the ulnar nerve as well as the fingers (Cambier et al, 1974;Bromm and Treede, 1980;Campbell et al, 1991;Bouhassira et al, 1993;Floeter et al, 1998;Serrao et al, 2006Serrao et al, , 2012Eckert and Riley, 2013). Such as for the lower limbs, this reflex activity could constitute a protective withdrawal response (Serrao et al, 2006;Peterson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the ''cutaneous silent period" (CSP), which is thought to be an inhibitory component of a defensive reflex (Inghilleri et al, 1997), can be evoked in the FDI muscle after noxious electrical stimulation of both the index (Floeter et al, 1998) and the hand dorsum (Romaniello et al, 2004;Kahya et al, 2010). Moreover, while the influence of limb position is well established for the lower limb (Andersen, 2007), few studies have investigated this for the upper-limb withdrawal reflex and have found inconsistent results (Eckert and Riley, 2013;Peterson et al, 2014). Mid-latency decrease of motor excitability at the stimulated hand Following the transient early-latency enhancement of the responses recorded in flexor hand muscles, there was a longer-lasting decrease of MEP amplitudes extending between 150 and 400 ms after the onset of the nociceptive stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the NWR is reflective of a protective sensorimotor response that is dependent on the location of the noxious stimulus as well as the position of the limb in space, relative to the body (136). While several studies have investigated upper extremity NWR characteristics in healthy adults while at rest (23,41,51,135,159) and with movement (159,204,205), or have focused on the NWR inhibitory period (cutaneous silent period) in hand muscles (83,91,99,158), no known studies have used a within-subjects, endogenous muscle pain model to investigate NWR adaptations in response to pain in multiple muscles of the upper extremity. Thus, our goal was to characterize the impact of muscle pain on the NWR in multiple muscles of the arm in order to advance understanding that may ultimately guide preventative and clinical pain interventions.…”
Section: What Does This Study Addmentioning
confidence: 99%